Wokół publikacji Wydawnictwa Karakter - Roś, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The purpose of this draft is to invite readers to read several novels, which Wydawnictwo Karakter from Cracow in the past few years introduced on the Polish publishing market. Joanna Ros explains why Karakter, popularizing the work of African writers, does the fancies of Albert Camus a favour. The novels cited by Joanna Roś testify to the fact that their authors are well acquainted with the literature of the author of The Plague and propose a completely new and unexpected encounters with it in the pages of his own works.